Quality improvement process to assess tattoo alignment, set‐up accuracy and isocentre reproducibility in pelvic radiotherapy patients - Elsner, Kelly (J Med Radiat Sci, 2014)
INTRODUCTION: This quality improvement study tested three methods of tattoo alignment and isocentre definition to investigate if aligning lateral tattoos to minimise pitch, roll and yaw decreased set‐up error, and if defining the isocentre using the lateral tattoos for cranio‐caudal (CC) position improved isocentre reproducibility. The study population was patients receiving curative external beam radiotherapy (EBRT) for prostate cancer. The results are applicable to all supine pelvic EBRT patients. METHODS: The three sequential cohorts recruited 11, 11 and 10 patients respectively. A data set of 20 orthogonal pairs of electronic portal images (EPI) was acquired for each patient. EPIs were matched offline to digitally reconstructed radiographs. In cohort 1, lateral tattoos were adjusted to minimise roll. The anterior tattoo was used to define the isocentre. In cohort 2, lateral tattoos were aligned to minimise roll and yaw. Isocentre was defined as per cohort 1. In cohort 3, lateral tattoos were aligned as per cohort 2 and the anterior tattoo was adjusted to minimise pitch. Isocentre was defined by the lateral tattoos for CC position and the anterior tattoo for the left–right position. RESULTS: Cohort 3 results were superior as CC systematic and random set‐up errors reduced from −1.3 mm to −0.5 mm, and 3.1 mm to 1.4 mm respectively, from cohort 1 to cohort 3. Isocentre reproducibility also improved from 86.7% to 92.1% of treatment isocentres within 5 mm of the planned isocentre. CONCLUSION: The methods of tattoo alignment and isocentre definition in cohort 3 reduced set‐up errors and improved isocentre reproducibility.